CXCL17 is a Mucosal Chemokine elevated in idiopathic pulmonary fibrosis that exhibits broad antimicrobial activity - Burkhardt, Amanda M. (2012)
The mucosal immune network is a crucial barrier preventing pathogens from entering the body. The network of immune cells that mediates the defensive mechanisms in the mucosa is likely shaped by chemokines, which attract a wide range of immune cells to specific sites of the body. Chemokines have been divided into homeostatic or inflammatory depending upon their expression patterns. Additionally, several chemokines mediate direct killing of invading pathogens, as exemplified by CCL28, a mucosa-associated chemokine that exhibits antimicrobial activity against a range of pathogens. CXCL17 was the last chemokine ligand to be described, and the 17(th) member of the CXC chemokine family. Its expression pattern in 105 human tissues and cells indicates that CXCL17 is a homeostatic, mucosa-associated chemokine. Its strategic expression in mucosal tissues suggests that it is involved in innate immunity and/or sterility of the mucosa. To test the latter hypothesis, we tested CXCL17 for possible antibacterial activity against a panel of pathogenic and opportunistic bacteria. Our results indicate that CXCL17 has potent antimicrobial activities, and that its mechanism of antimicrobial action involves peptide-mediated bacterial membrane disruption. Since CXCL17 is strongly expressed in bronchi, we measured it in bronchoalveolar lavage fluids, and observed that it is strongly upregulated in idiopathic pulmonary fibrosis. We conclude that CXCL17 is an antimicrobial mucosal chemokine that may play a role in the pathogenesis of interstitial lung diseases.